Crime and forgiveness christianizing execution in medieval Europe - Prosperi, Adriano 1939-; Carden, Jeremy (Cambridge, Massachusetts London, England The Belknap Press of Harvard University Press, 2020)
Cover -- Title Page -- Copyright -- Contents -- Preface to the English-Language Edition -- Preface -- Introduction: Justice-Revenge or Reconciliation? -- 1. Thou Shalt Not Kill -- 2. A Starting Point: Cesare Beccaria -- 3. The Law of Forgiveness, the Reality of Vengeance -- 4. The Murderer's Confession -- 5. The Earthly City, the Right to Kill, and the Ecclesiastical Power to Intercede -- 6. Bodies and Souls: Conflicts and Power Plays -- 7. Confession and Communion for the Condemned: A Rift between Church and State -- 8. Buried with Donkeys -- 9. A Special Burial Place -- 10. The Criminals' Crusade -- 11. "I Received His Head into My Hands -- 12. Factional Conflict and Mob Justice in the Late Middle Ages -- 13. "Holy Justice": The Turning Point of the Fifteenth Century -- 14. The Service -- 15. Political Crimes -- 16. Rome, a Capital -- 17. Reasoning on Death Row: The Birth and Development of the Arts of Comforting -- 18. A Charity of Nobles and the Powerful: The New Social Composition of the Companies -- 19. The Voices of the Condemned -- 20. Compassionate Cruelty: Michel de Montaigne and Catena -- 21. The Fate of the Body -- 22. Public Anatomy -- 23. Art and Spectacle at the Service of Justice -- 24. Capital Punishment as a Rite of Passage -- 25. The Arrival of the Jesuits: Confession and the Science of Cases -- 26. Laboratories of Uniformity: Theoretical Cases and Real People -- 27. Devotions for Executed Souls: Precepts and Folklore -- 28. Dying without Trembling: The Carlo Sala Case and the End of the Milanese Confraternity -- 29. Comforting of the Condemned in Catholic Europe -- 30. ". . . y piddiendo a Dios misericordia lo matan": The Jesuits and the Export of Comforting around the World -- 31. The German World, the Reformation, and the New Image of the Executioner -- 32. Printing and Scaffold Stories: Models Compared.
Keywords: Electronic books